The long walk - Bachman, Richard, 1947- (SIGNET, 1999)
"Finally available in a single volume edition under Stephen King's name! In the near future, a young boy has been one of 100 selected to take the Long Walk--a deadly contest of endurance and determination, in which each step can literally be your last. Follow the contestants' tortured footsteps as they struggle with each other, and themselves, to survive the race. Includes the Introduction "The Importance of Being Bachman". Vintage King, this harrowing tale was originally published under the Richard Bachman pseudonym."--Resumé vydavatele
"A Signet book."
Keywords: americké romány; thrillery (romány); American fiction; thrillers (novels)